The Problem of Intellectual Discourse in Contemporary Iraqi Painting (Post-War Experiences 2003-2022) ((An Analytical Study)) (Al-Academy, 2026)
The researcher starts in this field of research from the importance of the topic of the problem of intellectual discourse in contemporary Iraqi painting (post-war experiences 2003-2022) due to the aesthetic phenomenon it represents that has occupied an important space in the map of the visual discourse in its general form and painting in particular، and the research problem was determined through its manifestation in the following question: What is the problem of intellectual discourse in contemporary Iraqi painting? The importance of the current research lies in the fact that it sheds light on what is produced from thought on the visual surface in contemporary Iraqi painting by reviewing the structural levels in the visual discourse. As for the second chapter، the theoretical framework، it contained two sections: the first section / the concept of intellectual discourse، and the second section / intellectual variables in contemporary global and Iraqi painting. The third chapter contained the research procedures، including the research community، its sample، and the nature of the method in it، and then analyzing the sample، which amounted to (3) models. As for the fourth chapter، it contained the research results and conclusions، then the researcher came out with some recommendations and suggestions